THE SEARCH FOR THE LOST IDENTITY OF THE TRIBAL PEOPLE AND RELATING THEIR GRIEF WITH NATURAL PHENOMENON THROUGH SELECTED POETRY OF TRIBAL POETS OF NORTH BENGAL - JYOTIRMAY ROY (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The purpose of this study is to investigate the complex relationship that exists between the identity crisis that groups of tribal people in North Bengal are experiencing and the natural world that surrounds them, as reflected in a selection of poems written by tribal poets. Despite the forces of modernity, relocation, and marginalization, the indigenous people of this region have, for a very long time, tried to preserve their identity. They have distinct cultural traditions and traditional ways of living, and they have used them for generations. This yearning for a lost identity is emotionally articulated by the poets via their evocative lines. They frequently draw analogies between the loss that their society is experiencing and the natural events that are an essential part of their existence. The poems that were chosen for this investigation shed light on the profound link that exists between the identity of the indigenous people and the natural environment in which they live. The natural elements, which include rivers, woods, mountains, and animals, are not only backgrounds; rather, they are living creatures that reflect the sufferings, hopes, and resiliency of the tribal groups. Through an analysis of these poetry works, the purpose of this study is to discover how the poets make use of natural images and metaphors in order to convey the emotional and psychological upheaval that members of their communities are experiencing. In addition to this, it investigates the manner in which these poems function as a sort of resistance against the erasure of cultural traditions and as a means of recovering and maintaining their individuality. The ultimate goal of this research is to contribute to a more comprehensive understanding of how indigenous poetry from North Bengal not only reflects the lived experiences of the tribal people but also serves as a powerful tool in their ongoing struggle for cultural survival and self-affirmation in the face of overwhelming pressures from the outside world.